If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(u + -5) + -6 = -3(-6u + 9) + -3u Reorder the terms: 5(-5 + u) + -6 = -3(-6u + 9) + -3u (-5 * 5 + u * 5) + -6 = -3(-6u + 9) + -3u (-25 + 5u) + -6 = -3(-6u + 9) + -3u Reorder the terms: -25 + -6 + 5u = -3(-6u + 9) + -3u Combine like terms: -25 + -6 = -31 -31 + 5u = -3(-6u + 9) + -3u Reorder the terms: -31 + 5u = -3(9 + -6u) + -3u -31 + 5u = (9 * -3 + -6u * -3) + -3u -31 + 5u = (-27 + 18u) + -3u Combine like terms: 18u + -3u = 15u -31 + 5u = -27 + 15u Solving -31 + 5u = -27 + 15u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-15u' to each side of the equation. -31 + 5u + -15u = -27 + 15u + -15u Combine like terms: 5u + -15u = -10u -31 + -10u = -27 + 15u + -15u Combine like terms: 15u + -15u = 0 -31 + -10u = -27 + 0 -31 + -10u = -27 Add '31' to each side of the equation. -31 + 31 + -10u = -27 + 31 Combine like terms: -31 + 31 = 0 0 + -10u = -27 + 31 -10u = -27 + 31 Combine like terms: -27 + 31 = 4 -10u = 4 Divide each side by '-10'. u = -0.4 Simplifying u = -0.4
| -3y+15x=24 | | 20x-12xy+4xz= | | (6-2x)*(-4)=8 | | Tan(65)=x/10 | | 6x-6+2(2x+6)=-4(x+3) | | 7x-4+66=180 | | 4[x-8]=3x+5 | | (x-4)=(x+7) | | z+66=180 | | 30-4(6)= | | 2(4-3x)-3(2x+1)=7(5x+2)-103 | | 254=139-y | | 4a^3bx-4bx= | | tan(-x)=5/8 | | 8(0+2y)=16(30-4y) | | 9/-4=-2 | | 8x-34+118=180 | | 6x-0=-16 | | 0.5x-0.4y=2.6 | | -0.75+0.4= | | m^2+23m+24=1 | | 2(r+-130)+2r=1660 | | 3y+15x=24 | | 0.2x+0.3y=1.5 | | 5x+2(x-1)=6x-2 | | 3(r+-180)+3r=2340 | | -6f=-20 | | 3(r+-180)+4r=2340 | | a^3-6a^2= | | 16/9=x2 | | 20+6= | | 7x/3= |